Chronic and recurrent herpes zoster ophthalmicus - Lee, Soo Min; Han, Jisang; Yang, Chan Min; Choi, Chul Young; Khoramnia, Ramin; Chung, Tae-Young; Lim, Dong Hui (Medicina, 2021)
Background and Objectives: This study sought to investigate the natural course, the chronicity and recurrence rate, and the risk factors of chronic and recurrent herpes zoster ophthalmicus (HZO). We also evaluated the effects of long-term treatment for HZO. Materials and Methods: Patients diagnosed and treated for HZO were included in the retrospective medical chart review. Multivariable-adjusted logistic and Cox regression models were used to show risk factors for chronic and recurrent HZO along with hazard ratios (HRs) and 95% confidence intervals (CIs). Results: Among a total 130 of HZO patients, 31 patients (23.85%) had chronic disease and 19 patients (14.62%) had recurrent disease. The rate of chronic disease was higher in HZO with conjunctivitis, epithelial keratitis, and stromal keratitis. The recurrence rate increased in patients with chronic HZO (HR: 34.4, 95% CI: 3.6-324.6), epithelial keratitis (HR: 5.5, 95% CI: 1.3-30.0), stromal keratitis (HR: 18.8, 95% CI: 3.0-120.8), and increased intraocular pressure (IOP) (HR: 7.3, 95% CI: 1.6-33.2). Length of systemic antiviral therapy and anti-inflammatory eyedrop treatment were not associated with recurrent HZO (p = 0.847 and p = 0.660, respectively). The most common ocular manifestation for recurrent HZO was stromal keratitis. Conclusions: This study demonstrated a considerable frequency of chronic and recurrent HZO. Chronic HZO in the form of epithelial or stromal keratitis with increased IOP provoked a significant rise in the risk of recurrence.
Gesehen am 02.12.2021